Prevention of mother-to-child transmission of HIV practices by private general practitioners affiliated to the Aurum institutei - Shirley, Mashapha Thililelwi (My University, 2016)
Introduction: The mother-to-child transmission (MTCT) of HIV refers to the transmission of HIV from an HIV-infected woman to her child during pregnancy, labour, delivery or breastfeeding. This is the most common form of HIV transmission to infants and children. Without treatment, the likelihood of transmitting HIV from mother-to-child ranges between 15-45%. The national prevention of mother-to-child transmission (PMTCT) programme was first introduced in South Africa in 2001. Effective PMTCT programmes require women and their infants to receive a cascade of interventions including HIV testing during pregnancy, use of antiretroviral treatment (ART) by pregnant women living with HIV, safe childbirth practices and appropriate infant feeding, infant HIV testing and other post-natal healthcare services. The aim of this study was to describe Prevention of Mother-to-Child Transmission of HIV services among private general practitioners participating in a partnership programme with the Aurum Institute, assessing compliance to PMTCT Guidelines 2008 and 2010 as well as the MTCT rate at around six weeks. Methods: This was a retrospective review of records of women who enrolled into the PMTCT programme with the private general practioners affiliated to the Aurum Institute between January 2008 and April 2010. A total of 301 files of women enrolled on the PMTCT programme were reviewed. Data were collected from the women’s files and the Aurum database using a data abstraction form. Results: Even though HIV and TB guidelines were provided to all GPs, only less than 40% had copies of the guidelines in their general practice during the audit conducted in 2010. The GPs adhered to the 2008 and 2010 PMTCT Guidelines and even exceeded the NDoH target when it came to CD4 count testing and provision of lifelong ART to those who were eligible. In 2008, 91% of HIV positive pregnant women were tested for CD4 count, 99% were given lifelong ART and 74% of HIV exposed babies were tested at approximately six weeks by PCR. GPs did not adhere to guidelines in the provision of PMTCT prophylaxis where 21, 3% of women received prophylaxis and 77% of women received lifelong ART even though they were only eligible for prophylaxis. . GPs adhered to 2010 PMTCT guidelines regarding CD4 testing and provision of lifelong ART. Baseline CD4 count was completed in 93% of women and 94% received lifelong ART. In 2010, PCR testing was conducted in 66% of HIV exposed babies, which was lower than the NDoH target of 80%. The overall MTCT rate in this study was 1.8%; a lower MTCT rate among women who became pregnant on ART than those initiating ART during pregnancy (0% versus 3.2%). Conclusions and Recommendations: The GPs affiliated to The Aurum Institute showed good adherence to the PMTCT guidelines at most steps of the PMTCT cascade, for example: CD4 count testing and provision of ART. The study concludes that with proper training, support and mentoring, GPs can render comprehensive PMTCT services. The study also concludes that later initiation of ART had increased risk of MTCT and that women who received ART compared to prophylaxis had a lower MTCT rate. Further research is recommended to evaluate HIV and TB services rendered by GPs not affiliated or in private public partnership with any institution.
A Research Report submitted to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, South Africa, in partial fulfilment of the requirements for the Degree of Master of Public Health - Maternal and Child Health Submitted: February 2016